PENGARUH KERAGAMAN PRODUK, STORE IMAGE, DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN PADA TRI MART DI BLAHBATUH, GIANYAR - I Komang Ngurah Mudita; I Gusti Ayu Imbayani; I Made Surya Prayoga (VALUES, 2023)
Tri Mart Blahbatuh, Gianyar is one of the minimarkets that until now has been able to compete with similar minimarkets which are increasingly popping up, so to survive better it requires an increase in product variety, store image, and store atmosphere to provide convenience for consumers. This study aims to examine and obtain empirical evidence of the effect of product diversity, store image, and store atmosphere on purchasing decisions at Tri Mart in Blahbatuh, Gianyar. The population in this study is all consumers of Tri Mart in Blahbatuh, Gianyar whose exact number is not known. The sample used was 85 people with the accidental sampling method. The analytical tools used are multiple linear analysis, classical assumption test, t test, and F test. The results of this study indicate that product variety has a positive and significant effect on purchasing decisions, store image has a positive and significant effect on purchasing decisions, and store atmosphere has a positive and significant effect buying decision of Tri Mart in Blahbatuh, Gianyar.